A Case Study of Implementing Active Learning Techniques in Electrical Machine Course - Julius Fusic, S.; Kavitha, D.; Anandh, N. (Journal of Engineering Education Transformations, 2018)
Based on recent case studies, the faculties in engineering college are facing more struggle because how to make students to understand the concept clearly. So many faculties are failed to reach the students as facilitator. In some studies, students understand the concept which was taught by faculties, but fail to reproduce or remember the fundamentals during assessment period. In this paper, the improved teaching method for students to understand the concepts and remember the fundamentals through Active learning techniques (ALT). Here the techniques which explain the student's entertainments like games, puzzles, quiz, peer-to-peer learning and demonstration that are converted into education methods. Also few innovative ideas are implemented and examined on students. The active learning questionnaires, activities of students and experience over the activities are explained with the help of case studies, by taking two batch (2014&2016 – electrical machine course) of students and their performance are compared with and without the activities using active learning techniques. The comparison will be based on Blooms taxonomy assessment pattern results. However, the improvement of student's communications, selfconfidence level, interest towards the course, perspective thinking, team work, knowledge over the concept and course fundamentals are explained through these results.